Updating the Eifel record: zircon double-dating of tephras from Wehr volcano (East Eifel, Germany) as marker horizons for the European Pleistocene loess stratigraphy - Sturm, Anne; Schmitt, Axel Karl; Danišik, Martin (Quaternary science reviews, 2024)
Tephra marker horizons, originating from explosive volcanic eruptions, play a pivotal role in correlating disparate sedimentary records that offer insights into the dynamic fluctuations of Quaternary climate and the paralleling human evolution. The East Eifel volcanic field, Germany, produced multiple tephra layers, among which the Hüttenberg (HBT), Glees (GT), and Dümpelmaar (DMT) tephras, all associated with the Wehr volcanic center, serve as key marker horizons for the Pleistocene, occurring in multiple proximal to distal paleoenvironmental records. Published K-feldspar 40Ar/39Ar ages for HBT (215 ± 4 ka), GT (151 ± 11 ka), and DMT (116 ± 16 ka) have provided age constraints for central European loess-paleosol sequences, but these may be biased towards older ages due to suspected excess Ar or inherited crystals that were not completely degassed at the time of eruption. Here, we reassess the timing of crystallization and eruption from Wehr using coupled zircon 230Th/238U and (U-Th)/He geochronology, respectively. Error-weighted mean zircon crystallization ages are 230−23+28 ka for HBT (all uncertainties are 2σ), 169−11+23 ka for GT and 120−5+5 ka for DMT. In all cases, these are systematically older than corresponding zircon (U-Th)/He eruption ages of 193 ± 6 ka for HBT, 112 ± 3 ka for GT, and 99 ± 4 ka for DMT. Differences between published 40Ar/39Ar and (U-Th)/He ages are 22 ± 10 kyrs for HBT, 39 ± 14 kyrs for GT, and 17 ± 20 kyrs for DMT, exceeding three-sigma uncertainties for HBT and GT, whereas they overlap within uncertainty for DMT. Older zircon 230Th/238U ages indicate pre-eruptive crystallization in evolved residual melts and crystal residence over a timespan that matches the 40Ar/39Ar ages. Incomplete degassing of antecrystic feldspar experiencing pre-eruptive residence in a cool environment, possibly at the margins of an evolving magma reservoir, can explain this bias. The revised chronology shifts some of the Wehr tephras into younger paleoclimatic stages than previously assumed, readjusting the search window for potential cryptotephra studies. It also implies a shorter eruptive lull between that most evolved eruptions from Wehr and the subsequently active Laacher See volcano.
Gesehen am 28.11.2024